Pubarquia prematura. - Licea Puig, Manuel; Carvajal Alfonso, Matilde; Padrón Durán, Rubén S. (Revista Cubana de Pediatría, 2023)
Presenta los resultados obtenidos en el estudio de un grupo de pacientes portadores de pubarquia.